THE ROLE OF INTERTEXTUAL INCLUSIONS IN ENGLISH-LANGUAGE POLITICAL COMMUNICATION: https://doi.org/10.5281/zenodo.20823157 - Vishnyakova, Elizaveta (Scientific practical conference, 2026)
Political discourse is characterized by a fairly high degree of intertextuality. In English-language political communication, considerable attention is paid to intertextual inclusions borrowed from the speeches of political predecessors and used repeatedly by new politicians in new contexts, where semantic transformations are accompanied by the expectation of achieving value-oriented unity with the target audience based on a common volume and level of knowledge, including well-known realities and formulations that have occupied a firm place in the cultural and linguistic consciousness of society.